Understanding the reparative effects of schema modes: an in-depth analysis of the healthy adult mode - Yakın, Duygu; Arntz, Arnoud (Frontiers in Psychiatry, 2023)
Objective(s): Evidence in favor of schema therapy effectiveness in treating personality disorders is growing. One of the central and recently popular concepts of schema therapy is schema modes (i.e., temporary emotional-cognitive-behavioral states resulting from activation of an early maladaptive schemas (EMSs)). A key aspect herein is self-reparenting, i.e., a healing relationship between the Healthy Adult (HA, i.e., compassionate and healthy emotional states, and functional dealing with reality) and the child modes (i.e., representation of fragile and hurt feelings and dysfunctional coping).By an in-depth qualitative analysis, we aimed to better understand the components of the HA that enable self-reparenting.Purposive sampling procedures were used to recruit eligible participants (n=10) with relatively strong HA modes, as determined by high scores on positive affect and satisfaction with life measures, and low scores on EMSs and psychopathological symptom measures. Semi-structured 45-60-minute face-to-face interviews were conducted individually, in which individuals were asked to help the child modes reflected in pictures. Interviews were then analyzed using deductive thematic analysis in MaxQDA.Results. The analysis revealed three superordinate themes comprising of a total of 10 group themes: 1) bonding between HA and the vulnerable child modes ("Bond"); 2) balancing expression and inhibition of adult and child mode emotions ("Balance"); and 3) opposing demanding and critical voices and maladaptive coping styles ("Battle"). Furthermore, a strong HA mode seems to have a reciprocal relationship with the child modes: the HA gives nurturance and protection to the child modes, and the child modes boost up the HA with spontaneity and happiness.Conclusions. Emotional stability and resilience may be highest when HA-child mode interaction happens bidirectionally; when the child modes get reparented by the HA, and the HA is informed by the child modes.Schema therapy (ST) was originally developed as an integrative approach to treat complex, recurrent psychological problems and is (cost-)effective for personality disorders (PDs) in both individual